Respuesta :

5 - 3y = 6

y = -1/3

(5 - 3 * -1/3)^2

6^2 = 36

answer is 36

Answer:

36

Step-by-step explanation:

1. First, let's solve 5 - 3y = 6

Step 1: Subtract 5 from both sides.

  • [tex]5 - 3y - 5 = 6 - 5[/tex]
  • [tex]-3y = 1[/tex]

Step 2: Divide both sides by -3.

  • [tex]\frac{-3y}{-3} = \frac{1}{-3}[/tex]
  • [tex]y = -\frac{1}{3}[/tex]

2. Now, we plug in the value of y into (5 - 3y)^2

  • [tex](5 - 3(-\frac{1}{3}))^2[/tex]
  • [tex](5+(\frac{-3}{-3}))^2[/tex]
  • [tex](5+1)^2[/tex]
  • [tex](6)^2[/tex]
  • [tex]36[/tex]

Therefore, the missing number is 36.